Analisis Kesulitan Belajar Matematika pada Materi Diagram Batang Siswa Kelas IV SDN Kalicari 01 Semarang - Zahro, Fatimatuz; Patonah, Siti; Rofiatun, Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Mathematics learning is considered challenging for many students, with some sh. owing little interest or motivation to engage with the subject. This is often due to difficulties encountered during the learning process. This study aims to analyze students' difficulties in learning Mathematics, specifically focusing on bar diagram topics. The research employs a qualitative method with a descriptive approach. Data collection techniques include interviews, observations, and documentation. Data analysis involves data collection, data reduction, data presentation, and drawing conclusions. Findings from the study reveal that the majority of Grade IVA students at SDN Kalicari 01 Semarang experience difficulties in remembering technical terms such as X-axis, Y-axis, and frequency. They also struggle with explaining bar diagram concepts in their own words and recalling the steps involved in creating bar diagrams. Efforts to address these challenges include implementing a more structured learning approach, actively interacting with class and support teachers for guidance, and utilizing aids or interactive media to enhance student engagement and comfort in learning. Additionally, remedial activities are conducted to help students improve their grades and assist teachers in assessing student learning progress